2018
DOI: 10.3390/rs10010129
|View full text |Cite
|
Sign up to set email alerts
|

Impacts on the Urban Environment: Land Cover Change Trajectories and Landscape Fragmentation in Post-War Western Area, Sierra Leone

Abstract: An influential underlying driver of human-induced landscape change is civil war and other forms of conflict that cause human displacement. Internally displaced persons (IDPs) increase environmental pressures at their destination locations while reducing them at their origins. This increased pressure presents an environment for increased land cover change (LCC) rates and landscape fragmentation. To test whether this hypothesis is correct, this research sought to understand LCC dynamics in the Western Area of Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 52 publications
7
32
0
Order By: Relevance
“…ecocide) (Le Billon 2001, McNeely 2003, Hanson and Machlis 2008, Butsic et al 2015. As many studies have documented forest cover change during communal, intra-state, and inter-state conflicts (Stevens et al 2011, Gorsevski et al 2012, Wilson and Wilson 2013, Nackoney et al 2014, Butsic et al 2015, Gbanie et al 2018, Sung et al 2019, Yin et al 2019, the idiosyncratic and diverse effects of conflict on forest cover have become well-defined (Ordway 2015, Baumann and Kuemmerle 2016, Hanson 2018, Grima and Singh 2019, Landholm et al 2019. However, much less is known about forest cover change processes following the cessation of conflict or the signing of a peace agreement between warring factions.…”
Section: Introductionmentioning
confidence: 99%
“…ecocide) (Le Billon 2001, McNeely 2003, Hanson and Machlis 2008, Butsic et al 2015. As many studies have documented forest cover change during communal, intra-state, and inter-state conflicts (Stevens et al 2011, Gorsevski et al 2012, Wilson and Wilson 2013, Nackoney et al 2014, Butsic et al 2015, Gbanie et al 2018, Sung et al 2019, Yin et al 2019, the idiosyncratic and diverse effects of conflict on forest cover have become well-defined (Ordway 2015, Baumann and Kuemmerle 2016, Hanson 2018, Grima and Singh 2019, Landholm et al 2019. However, much less is known about forest cover change processes following the cessation of conflict or the signing of a peace agreement between warring factions.…”
Section: Introductionmentioning
confidence: 99%
“…Since landscape pattern influences the functioning and provision of ecosystem services [47,57,58], changes in spatial pattern quantified by landscape metrics can act as indicators of impact on ecosystem services [56,59]. Landscape metrics have an established record as tools to measure spatial heterogeneity in landscapes [60][61][62][63] and have been used to estimate fragmentation in urbanizing landscapes [64][65][66][67]. Lausch et al [68] have found that high hemeroby (low naturalness and high human pressure on landscapes) reduces heterogeneity in space and time within patterns and the patch matrix model, which constitutes the framework for calculation of landscape metrics, is recommended for analysis of these kinds of, most notably urban, landscapes.…”
Section: Urban Environmental Impact Analysismentioning
confidence: 99%
“…A total of seven SWAT parameters were calibrated. (Wilson and Wilson, 2013;Wilson, 2014;Gbanie et al, 2018). Growth in agricultural land after 2010 was further amplified by the acquisition of a huge swath of land in the southeastern portion of the watershed (figure 3b) for commercial sugarcane plantation in support of a major biofuel industrial operation (Maconachie and Fortin, 2013) …”
Section: Distributed Hydrologic Flow Model Constructionmentioning
confidence: 99%